A Conversation Analysis of self-initiated repair structures in Jordanian Spoken Arabic. (August 2015) - Al-Harahsheh, Ahmad Mohammad Ahmad
This article studies the Conversation Analysis (CA) of self-initiated repair structures in everyday conversations in Jordanian Spoken Arabic (JSA). It aims to cast light on self-initiated repairs practised by Jordanians. The data were collected in 2010; 18 dyadic-videotaped conversations totalling about nine hours, mixed and single-sex, were conducted at Yarmouk University, Irbid, Jordan. The data analysed include 1595 self-initiated repairs. The CA approach is employed as a theoretical framework for this study. The findings of this research indicate that Jordanian speakers practise 10 self-initiated repair structures, namely, expansion, hesitation, replacement, repetition, abort and restart, abort and abandon, insertion, deletion, meta-repair and modify order.